AUTOMATION OF WELDING PLANTS AT AUTOMOBILE PLANTS: IMPROVEMENT PATHS AND ECONOMIC EFFECT - Juraev Abdullajon Ibragimovich (Bright Mind Publishing, 2025)
Automation of welding processes is a key factor in increasing the efficiency and quality of production at automobile plants. This work is devoted to analyzing the current state of automation of welding sections in the automotive industry, studying promising directions for improving technologies, and assessing the economic effect of implementing automated solutions. The article examines various types of welding equipment used in the automotive industry, their advantages and disadvantages, as well as modern methods of controlling and monitoring welding processes.
Keywords: Automation, welding, automotive manufacturing, robotics, welding equipment, machine vision, artificial intelligence, economic effect, production optimization, welding quality, productivity.